The Linkage Between Speculative Attack and Target Zone Models of Exchange Rates. (IMF Working Papers; Working Paper, 1989)
In this paper we generalize the target zone exchange rate as model formalized by Krugman (1988b). The main contributions of these pages consist of linking the recent developments in the theory of target zones to the mirror image theory of speculative attacks on asset price fixing regimes and in using aspects of that linkage to give an intuitive interpretation to the 'smooth pasting' condition often invoked as a terminal condition. We aim to unify these two literatures by showing that the solution concepts in both are identical.